2007
DOI: 10.1002/cyto.a.20469
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric assessment of DNA damage by exogenous and endogenous oxidants reports aging‐related processes

Abstract: The ongoing DNA damage caused by reactive oxygen species generated during oxidative metabolism is considered a key factor contributing to cell aging as well as preconditioning cells to neoplastic transformation. We postulated before that a significant fraction of constitutive histone H2AX phosphorylation (CHP) and constitutive activation of ATM (CAA) seen in untreated normal and tumor cells occurs in response to such DNA damage. In the present study, we provide further evidence in support of this postulate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
98
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(116 citation statements)
references
References 70 publications
(103 reference statements)
17
98
1
Order By: Relevance
“…28 In the case of Cep, activation of NFκB, which is a redox-sensitive transcription factor, 70 seems to be prevented by the antioxidant action of this alkaloid. [50][51][52][53][54] Antioxidant properties of Onc 56 could additionally lower the redox potential within the cell providing further hindrance in activation of NFκB. Simultaneous inactivation of NFκB by diverse mechanisms as offered by Onc and Cep, respectively, may be so effective that it completely eliminates expression of the "survival genes."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In the case of Cep, activation of NFκB, which is a redox-sensitive transcription factor, 70 seems to be prevented by the antioxidant action of this alkaloid. [50][51][52][53][54] Antioxidant properties of Onc 56 could additionally lower the redox potential within the cell providing further hindrance in activation of NFκB. Simultaneous inactivation of NFκB by diverse mechanisms as offered by Onc and Cep, respectively, may be so effective that it completely eliminates expression of the "survival genes."…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] We have recently reported that Cep effectively scavenges endogenous oxidants generated during aerobic metabolism, protecting DNA from oxidative damage. 53,54 The radicals scavenging properties of Cep may mediate several of the effects listed above, such as inhibition of the lipid peroxidation, 43 protection from carcinogens, 49 anti-inflammatory properties 41 or protection from radiotherapyinduced leucopenia. 39 It was recently reported that Cep sensitizes human oral carcinoma cells to radiation by inhibiting activation of NFκB.…”
Section: Introductionmentioning
confidence: 99%
“…These include cell shrinkage, nuclear condensation, internuclosomal DNA cleavage, and apoptotic signaling cascades that may be detected by multicolor immune fluorescence cytometry. Moreover, cytometry offers the possibility to measure intravitally mitochondrial membrane potential, generation of reactive oxygen species, Ca 21 content, caspase activity, and phosphatidylserine externalization (82,83).…”
Section: Cell Death Drug Testing and Toxicologymentioning
confidence: 99%
“…DNA damage, if not repaired, accumulates with age which contributes to cell senescence and preconditions to neoplasia development. The introduction of the sensitive DNA damage reporters for cytometric assessment may facilitate and accelerate drug development (82).…”
Section: Cell Death Drug Testing and Toxicologymentioning
confidence: 99%
See 1 more Smart Citation